Quality of Life (QoL) in a Brazilian Sample of Older Adults: The Role of Sociodemographic Variables and Depression Symptoms - Trentini, Clarissa Marceli; Chachamovich, Eduardo; Wagner, Gabriela Peretti; Müller, Daniela Helena; Hirakata, Vânia Naomi; de Almeida Fleck, Marcelo Pio (Applied Research in Quality of Life, 2011)
The aim of the present study was to identify relevant variables associated with Quality of Life (QoL) in older adults. Older adults, up to 60 years old, were interviewed. Subjects were recruited through convenience sampling. 339 paticipants, who were stratified by gender, age, and subjective perception of health and illness, answered questions on sociodemographic issues, QoL (WHOQOL-100) and depressive symptomathology (Beck Depression Inventory—BDI). The multiple linear regression analysis showed associations of overall perception of QoL with depression levels, subjective perception of health status and gender. The individual analysis of each domain concluded that depression levels are correlated to all QoL domains, while health status was associated with physical, psychological, independence level and social relationship domains. Other variables were also assessed. The assessment of older adults concerning their QoL perceptions is associated with gender, age, marital status, social class, literacy rate, perception of health, and more substantially associated with depressive symptoms levels. Nevertheless, some limitations of this study and further ones are suggested.